Robust Optimization for Misalignment Tolerance in Inductive Power Transfer Coupler Design - Sampath Jayalath; Azeem Khan (IEEE Open Journal of the Industrial Electronics Society, 2023)
Coupler parameters, such as transmitter inductance (LTx), receiver inductance (LRx), and the coupling coefficient (k) or mutual inductance (M), vary with the misalignments. Their variations must be quantified and incorporated into the design and optimization stage as they impact performance indices such as efficiency and leakage magnetic field. Most of the solutions proposed in the literature compromise the performance of the coupler in search of a misalignment-tolerant design. Therefore, this article presents a method to incorporate the misalignments into the design and optimization process of an inductive power transfer (IPT) coupler by utilizing robust optimization, where misalignments are considered as noises or disturbances or uncertainties to a perfectly aligned coupler. The optimized designs resulting from this method will not compromise the performance of the coupler in search of a misalignment-tolerant design. Effectiveness of the proposed robust optimization method is experimentally verified with a 3.7 kW hardware prototype.